Efficacy of Mosquito Coils: Cross-resistance to Pyrethroids in Aedes aegypti (Diptera: Culicidae) From Indonesia - Amelia-Yap, Zheng Hua; Chen, Chee Dhang; Sofian-Azirun, Mohd; Lau, Koon Weng; Suana, I Wayan; Harmonis, -; Syahputra, Edy; Razak, Abdul; Low, Van Lun (Oxford University Press, 2018)
Aedes aegypti (L.) (Diptera: Culicidae) is the primary vector of several arthropod-borne viral infectious diseases globally. Relentless vector control efforts are performed to curtail disease transmissions, insecticides remain as the first line of defense in Indonesia. With a dearth of publication on the efficacy of mosquito coil in Indonesia, this is the first report related to mosquito coil despite its common use in households. Ae. aegypti mosquitoes were sampled from nine regencies in Indonesia and tested using the glass-chamber method against three commercially available local pyrethroid-based mosquito coils containing d-allethrin, transfluthrin, and metofluthrin. The 50% knockdown time of female Ae. aegypti tested with d-allethrin, transfluthrin, and metofluthrin containing coils ranged from 0.65 to 14.32; 0.8 to 16.4; and 0.78 to 20.57 min, respectively. Mortality rates in accordance with WHO resistance indicators showed that strains from Denpasar, Mataram, Kuningan, Padang, Samarinda, and Sumba Timur were resistant (<80% mortality rate), whereas strains from Manggarai Barat, Dompu, and Pontianak were susceptible (>98% mortality rate) to the active ingredients assayed. Moreover, the knockdown rates between d-allethrin and transfluthrin, d-allethrin and metofluthrin, as well as transfluthrin and metofluthrin displayed significant associations, portraying the presence of cross-resistance within pyrethroid insecticides. The minimal insecticidal effect of mosquito coils against some Indonesian Ae. aegypti also pointed out the development of pyrethroid resistance, prompting a revamping of the vector control system.